Trabalhadores de frigorífico: trabalho, lazer e moradia (1960-1980) - Pereira, Fagner Guglielmi (2014)
This dissertation discusses the experience of workers who worked in a slaughterhouse pigs in Marechal Cândido Rondon-PR during the years 1960-1980. They migrated from very different regions of Brazil. The analysis of their experiences revealed the ways of life and work before and after of the work in the slaughterhouse. During the 1970s, the economy integration of countryside and town approached of the productions the settlers. In the town, were installed grain processing factories and slaughterhouse. The economy between countryside and the town was based the installation of factories for the benefit of soybeans and industrialization of the pig meat. This process, changed ways of living and working and constituted new working relationships and ways of living. To arrive at this diagnosis, it was necessary to investigate the lives of workers who migrated to the West Paranaense region amid the transformation of economic scenario in Marechal Cândido Rondon-PR and region. The trajectories of life of workers and the their experiences with working in the historical context of industrial constitution in the west of the Paraná. From this paper will explicate: life trajectories of migrant workers, occupations in the industrial activity, senses and meanings about work and life in the the Workers' Village in Marechal Cândido Rondon-Pr